Utilization of telehealth in paediatric genome-wide sequencing: Health services implementation issues in the CAUSES Study. (May 2023) - Elliott, Alison M; Dragojlovic, Nick; Campbell, Teresa; Adam, Shelin; Souich, Christèle du; Fryer, Michele; Lehman, Anna; Karnebeek, Clara van; Lynd, Larry D; Friedman, Jan M
Introduction: Genome-wide sequencing (exome or whole genome) is transforming the care and management of paediatric patients with a rare disease because of its diagnostic capabilities. Genome-wide sequencing is most effective when both parents and the child are sequenced as a trio. Genetic counselling is recommended for all families considering genome-wide sequencing. Although telehealth is well established in genetic counselling for hereditary cancer and prenatal genetics, its use with genome-wide sequencing has not been well studied. The CAUSES Clinic at BC Children's and Women's Hospitals was a translational paediatric trio-based genome-wide sequencing initiative. Pre-test genetic counselling via telehealth (at a clinical site near the family's residence) was offered to families who had been previously evaluated by a clinical geneticist. We report on the first 300 families seen in the CAUSES clinic and compare health services implementation issues of families seen via telehealth versus on-site. Methods: Demographics, cost to families (travel and time), time to first appointment, complete trio sample accrual and diagnostic rates were studied. Results: Of the 300 patients, 58 (19%) were seen via telehealth and 242 (81%) were seen on-site for pre-test counselling. The mean time to completion of accrual of trio samples in the telehealth group was 56.3 (standard deviation ±87.3) days versus 18.9 (standard deviation ±62.4) days in the onsite group ( p < 2.2 × 10 −16 ). The mean per-family estimated actual or potential travel/time cost savings were greater in the telehealth group (Can987; standard deviation = Can1151) than for those seen on-site (Can305; standard deviation = Can589) ( p = 0.0004). Conclusions: Telehealth allowed for access to genome-wide sequencing for families in remote communities and for them to avoid significant travel and time costs; however, there was a significant delay to accrual of the complete trio samples in the telehealth group, impacting on time of result reporting and delaying diagnoses for families for whom genome-wide sequencing was diagnostic.